2014
DOI: 10.1245/s10434-014-3682-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathology Review Significantly Affects Diagnosis and Treatment of Melanoma Patients: An Analysis of 5011 Patients Treated at a Melanoma Treatment Center

Abstract: Diagnosis, AJCC T classification, and treatment recommendations often change after pathology review by specialist melanoma pathologists. We recommend pathology review be considered for all patients attending specialist melanoma treatment centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 33 publications
2
40
1
Order By: Relevance
“…Previous studies were constrained by small numbers of cases (eg, ≤20), 6 24-26 non-randomly selected cases, [27][28][29][30][31][32][33][34][35][36][37] narrow disease spectrum of cases, 5 Numbers of diagnostic interpretations with intraobserver agreement are emboldened. *Concordance rates are influenced by case composition, which included larger proportions of cases in classes II-V than would typically be encountered in practice.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Previous studies were constrained by small numbers of cases (eg, ≤20), 6 24-26 non-randomly selected cases, [27][28][29][30][31][32][33][34][35][36][37] narrow disease spectrum of cases, 5 Numbers of diagnostic interpretations with intraobserver agreement are emboldened. *Concordance rates are influenced by case composition, which included larger proportions of cases in classes II-V than would typically be encountered in practice.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…1,3 Moreover, epidemiologic research regarding melanocytic lesions and associated outcomes has been limited by diagnostic inconsistency. Treatment suggestions in pathology reports may help resolve this ambiguity.…”
Section: Introductionmentioning
confidence: 99%
“…e-mail: susan.davies@addenbrookes.nhs.uk cases reported by general pathologists found clinically significant discrepancies in only 1.4% of reviews, 12 but an expert review of melanoma diagnoses in patients referred to a specialist centre identified clinically significant diagnostic differences in 5% of cases, discrepancies in staging in an additional 22%, and consequently changes in management in 20% of patients. 13 It is standard UK practice for patients with a cancer diagnosis to be discussed at a multidisciplinary team (MDT) meeting, involving a review of any histopathology, prior to deciding on management. Recent studies in a range of diagnoses, including prostate cancer, breast cancer, lymphoma and melanoma, have demonstrated the value of this, with discrepancy rates varying from 6% to 57% [13][14][15][16][17] and involving the malignant diagnosis itself, or the classification, stage or grade of the tumour.…”
Section: Introductionmentioning
confidence: 99%
“…13 It is standard UK practice for patients with a cancer diagnosis to be discussed at a multidisciplinary team (MDT) meeting, involving a review of any histopathology, prior to deciding on management. Recent studies in a range of diagnoses, including prostate cancer, breast cancer, lymphoma and melanoma, have demonstrated the value of this, with discrepancy rates varying from 6% to 57% [13][14][15][16][17] and involving the malignant diagnosis itself, or the classification, stage or grade of the tumour. Changes in patient management were predicted in 6-22% of all cases reviewed.…”
Section: Introductionmentioning
confidence: 99%